A role for BDNF/TrkB signaling in behavioral and physiological consequences of social defeat stress - Razzoli, M.; Domenici, E.; Carboni, L.; Rantamaki, T.; Lindholm, J.; Castrén, E.; Arban, R. (Genes, brain and behavior, 2011)
Accumulating evidences underlie the importance of the interplay between environmental and genetic factors in contributing to the risk to develop mental illness. Brain‐derived neurotrophic factor (BDNF) and its Tyrosine receptor kinase B (TrkB) receptor play a fundamental contribution to brain development and plastic adaptations to life events. In the present study, the potential for the BDNF/TrkB contribution in increasing vulnerability to negative social experiences was assessed by subjecting TrkB.T1 overexpressing mice to a chronic social defeat model. TrkB.T1 mice overexpress the dominant‐negative truncated splice variant of TrkB receptor leading to decreased BDNF signaling. After repeated social defeat, mice were assessed in a longitudinal study for behavioral, physiological, endocrine and immune responses potentially related to psychiatric endophenotypes. TrkB.T1 overexpression corresponded to smaller changes in metabolic parameters such as body weight, food intake, feed efficiency and peripheral ghrelin levels compared with wild‐type (wt) littermates following social defeat. Interestingly, 4 weeks after the last defeat, TrkB.T1 overexpressing mice exhibited more consistent social avoidance effects than what observed in wt subjects. Finally, previously unreported effects of TrkB mutations could be observed on lymphoid organ weight and on peripheral immune biomarker levels, such as interleukin‐1α and regulated on activation, normal, T‐cell expressed, and secreted (RANTES), thus suggesting a systemic role of BDNF signaling in immune function. In conclusion, the present data support a contribution of TrkB to stress vulnerability that, given the established role of TrkB in the response to antidepressant treatment, calls for further studies addressing the link between stress susceptibility and variability in drug efficacy.